Analysis of the Application of Green Building Concepts in Educational Buildings Case Study: Building B, Faculty of Biology UGM Yogyakarta - Ayuningtyas, Nurina Vidya; Adianti, Istiana (Jurnal Teknik Sipil dan Perencanaan, 2022)
Abstract. The building sector is one of the world's largest energy consumers. This problem is further exacerbated by our dependence on non-renewable energy sources. More than 90% of the world's energy comes from fossil energy including oil, natural gas and coal whose availability in nature continues to decrease because they cannot be renewed. Green design is a reaction to the global environmental crisis. Green design which also leads to eco design, or design for environment is the art of designing physical objects and the surrounding environment to balance sustainable principles with economic, social, and ecological aspects. As a construction actor, you are required to be able to produce a building design that does not require too much energy consumption and also of course considers the comfort of the occupants in it. In an effort to develop the campus, Universitas Gadjah Mada seeks to make the UGM campus a Green Campus. One of the buildings at UGM and the first building at UGM to be certified as a green building by the Green Building Council Indonesia (GBCI), namely Building B, Faculty of Biology UGM with 43% energy savings points, 30% water and 65% efforts to utilize local materials . From the Energy sector, this building applies a small percentage of window/glass openings, uses reflective paint so as to minimize heat that will be transmitted into the building, external shading devices (shading), applies insulation on the roof, a variable refrigerant type HVAC system (VRF). ) with a high COP so that it can save more energy and use artificial lighting / energy-saving lamps. From the water sector, using a toilet fixture with a low flow so that it can save water. Meanwhile, the use of materials includes the use of clay tiles, hebel walls and other materials that are local products.